2020
DOI: 10.1292/jvms.19-0643
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles from rat plasma promote migration and proliferation of vascular smooth muscle cells

Abstract: Small extracellular vesicles (sEV) contain various molecules and mediate cell-to-cell communication under both physiological and pathological conditions. We have recently reported that sEV isolated from plasma of normotensive Wistar Kyoto rats (WKY) and spontaneously hypertensive rats (SHR) regulate systemic blood pressure. The initiation and development of hypertension partly rely on proliferation and migration of vascular smooth muscle cells (SMCs) followed by the structural remodeling of vascular wall. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…It remains to be clarified whether sEV are stable in circulation for 24 hr. We previously confirmed that sEV were uptaken into VSMC within 2 hr [16] and that they were remaining within the cells after 24 hr. Since we focused on the effects of small RNA including microRNA in sEV, which mediates the protein expression in the recipient cells, we examined the long-term effects of sEV.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…It remains to be clarified whether sEV are stable in circulation for 24 hr. We previously confirmed that sEV were uptaken into VSMC within 2 hr [16] and that they were remaining within the cells after 24 hr. Since we focused on the effects of small RNA including microRNA in sEV, which mediates the protein expression in the recipient cells, we examined the long-term effects of sEV.…”
Section: Discussionsupporting
confidence: 52%
“…sEV were isolated from plasma of WKY (WsEV) and SHR (SsEV) by the precipitation with polyethylene-glycol and ultracentrifugation as previously described [ 15 , 16 ]. WKY and SHR (8-week-old) were deeply anesthetized with urethane (Sigma-Aldrich, St. Louis, MO, USA) (1.5 g/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein expression in NRCFs-derived EV, NRCFs, and NRCMs was determined by Western blotting as previously described [23,25]. After 10 equal amounts of protein were separated by SDS-PAGE (7.5-14%, 80-120 V, 1.5 hr), they were transferred to a nitrocellulose membrane (Pall Corporation, Ann Arbor, MI, USA) (400 mA, 1.5 hr).…”
Section: Western Blottingmentioning
confidence: 99%
“…EVs include three distinct particles such as exosomes, microparticles or microvesicles, and apoptotic bodies ( Noble et al, 2020 ; Swatler et al, 2020 ). Recent studies reported that VSMC proliferation and migration are regulated by EVs derived from ECs ( Ryu et al, 2019 ) as well as from other sources including plasma ( Otani et al, 2020 ), fibroblasts ( Ren et al, 2020 ), macrophages ( Niu et al, 2016 ; Sharma et al, 2018 ), and adipose mesenchymal stem cells ( Liu et al, 2016 ). EVs are known to contain and carry various bioactive molecules, including proteins, lipids, and nucleic acids ( Berezin and Berezin, 2020 ; Xing et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%